PENDEKATAN PENDIDIKAN DALAM STUDI ISLAM - Ahmad Labib (Istifkar: Media Transformasi Pendidikan, 2021)
In studying Islam, several approaches can be used, one of which is the educational approach. The educational approach in Islamic studies is one of the paradigms or one's point of view used in interpreting Islamic values through education with a focus on forming a complete human being and having faith in Allah SWT. Without an approach, it will be very difficult for everyone to understand and understand. The method used in this research is to use library research or library research which takes several references or libraries according to the themes discussed. The discussion of the educational approach in Islamic studies or studies is inseparable from the approach of moral education because actually in Islam or what is contained in the Qur'an or the hadith of the Prophet Muhammad himself has taught or described education whose educational orientation is to achieve goodness or happiness. in this world and the hereafter. And among the moral or moral education that can be achieved is the cultivation of values, cognitive moral   development, value analysis, value explanation, affection approach and cooperative learning approach.